Being seen or being endorsed: Institutional and individual voices in China’s public diplomacy on Twitter - Fangyuan Che; Qian Qin; Linjiang Guo (International Political Science Review, 2026)
Since the 2010s, China’s public diplomacy rhetoric has undergone the shift from a traditionally restrained approach to a more assertive and confrontational style known as ‘wolf warrior’ diplomacy. This paper discusses these developments within the broader context of digital diplomacy, where social media platforms like Twitter have become essential arenas for international discourse and influence. While previous research has largely defined social media success as visibility metrics such as likes and replies, this paper argues that visibility does not necessarily translate into endorsement. Combining LLM-based stance detection with network topology analysis, this paper reveals a structural paradox. While institutional accounts successfully use ‘wolf warrior’ rhetoric to close the visibility gap with individual diplomats, they struggle to convert attention into endorsement. Individual accounts, by contrast, demonstrate higher mobilization capacity, cultivating denser supporter networks. In the attention economy of global social media, being seen is not equivalent to being endorsed.